Cholesterol granuloma of the maxillary sinus in association with a dental implant—A case report. (18th October 2022) - Vikram, Vignesh; Raja, Sunitha; Ramanathan, Manikandhan
Abstract: Background: Cholesterol granuloma is typically a benign granulomatous growth seen mostly in the mastoid process and the petrous temporal bone. Although cholesterol granuloma in maxillary sinus was first reported in the scientific literature in 1978, the occurrence is very rare and it is usually clinically and radiographically manifested ambiguously as maxillary sinusitis. Purpose: The presence of cholesterol granuloma in the maxillary sinus in association with a dental pathology or prosthesis has been scarcely known. In this case report, we present a case of cholesterol granuloma in the maxillary sinus of a middle‐aged male who had previously undergone dental implant placement in relation to that anatomical location. Materials and Methods: A 64‐year‐old man reported to the Dental OP with a chief complaint of oral malodor, swelling, and tenderness over the right middle third of the face for the past 3 months. A cone beam computed tomography scan showed a well‐defined radio‐opaque lesion along with sclerosis and thinning of bone within the right maxillary antrum in relation to the dental implant placed in the 16 regions. The left maxillary sinus appeared normal. The Caldwell‐Luc procedure was performed and a solitary soft lesion with yellowish‐gray contents was evident within the right maxillary sinus. Histopathological examination revealed cholesterol clefts surrounded by foreign body giant cell reaction and granulation tissue formation, along with the presence of old and recent hemorrhage. A final diagnosis of cholesterol granuloma was made based on the histopathological examination report. Conclusion: Based on the evidence available in the present case, we hypothesize that the localized trauma and hemorrhage initiated by implant placement in this particular anatomical location could have plausibly resulted in the occurrence of cholesterol granuloma in our patient.